A supervisory Volt/Var control scheme for coordinating voltage regulators with smart inverters on a distribution system - Muthukaruppan, Valliappan; Shi, Yue; Baran, Mesut (Frontiers in Smart Grids, 2024)
This paper concentrates on the efficient utilization of smart inverters for Volt/Var control (VVC) within a distribution system. Although new smart inverters possess Var support capability, their effective deployment necessitates coordination with existing Volt/Var schemes. To address this, a novel VVC scheme is proposed to facilitate such synchronization. The proposed scheme bifurcates the issue into two levels. The initial level involves utilizing Load Tap Changer (LTC) and Voltage Regulators (VRs), coordinating their control with smart inverters to regulate the circuit's voltage levels within the desired range. The subsequent level determines the Var support required from smart inverters to minimize overall power loss in the circuit. The supervisory control results are communicated to the respective devices equipped with their local controllers. To minimize frequent dispatch, smart inverters are supervised by adjusting their Volt/Var characteristics as necessary. This approach enables the smart inverters to operate near their optimal control while meeting the limited communication prerequisites in a distribution system. A case study employing the IEEE 34 bus system illustrates the efficacy of this supervisory control scheme in contrast to traditional volt/var schemes.